Physicochemical and sensory analysis of Syrah wines from vineyards mechanically pruned treated with different organic amendments - Pardal, Rafaela Alexandra Cerqueira (2016)
Mestrado em Viticultura e Enologia - Instituto Superior de Agronomia / Faculdade de Ciências. Universidade do Porto